PENGARUH LITERASI EKONOMI, E-COMMERCE, EKSPEKTASI PENDAPATAN TERHADAP MINAT BERWIRAUSAHA PADA GENERASI Z DI JAKARTA - Muflihina, Isma; Sebayang, Karuniana Dianta Arfiando; Iranto, Dicky (Bhinneka Multidisiplin Journal, 2025)
This study aims to: (1) Knowing the significant effect of economic literacy on entrepreneurial interest in generation z in Jakarta (2) Knowing the effect of e-commerce on entrepreneurial interest in generation z in Jakarta (3) Knowing the effect of income expectations on entrepreneurial interest in generation z in Jakarta. This research is a descriptive quantitative research with a quantitative approach. The research instrument used a questionnaire. The data used is primary data obtained by distributing questionnaires online to 272 respondents with Random Sampling technique and data processing is done with SPSS 22 with multiple linear regression analysis techniques. The results of this study indicate that simultaneously economic literacy, e-commerce, and income expectations affect entrepreneurial interest in generation z in Jakarta. Partially, economic literacy has a positive and significant effect on entrepreneurial interest in generation z in Jakarta. Partially e-commerce has a positive and significant effect on entrepreneurial interest in generation z in Jakarta. Partially, income expectations have a positive and significant effect on entrepreneurial interest in generation z in Jakarta. Based on the above research results that economic literacy, e-commerce, and income expectations have a major influence on entrepreneurial interest in generation z in Jakarta.